Women’s development organisations in rural areas of Tunisia: rethinking support to strengthen their autonomy - Hanafi Anissa; Mazhoud Houda; Chemak Fraj; Faysse Nicolas; Kharroubi Fatma (Cahiers Agricultures)
Women’s development organisations in rural areas of Tunisia were first created in the early 2010s, since when their number has increased steadily. These organisations have received wide-ranging support from public and non-governmental development actors, which has helped them develop but has also compromised their autonomy, i.e. their capacity to fix objectives on their own and to contact other actors only when needed to achieve their objectives. The present study analyses the development trajectory and autonomy of women’s development organisations in Siliana Governorate. Most of the activities of the nine organisations studied concern the collective production and marketing of a variety of products related to animal breeding, food, and handicrafts. Since their creation, most organisations have increased their number of members and their range of activities. In a workshop in which presidents of these organisations, their members, and administrative support staff took part, participants pointed out that the members’ technical and management skills, their willingness and ability to organise collective action play a key role in ensuring the autonomy of the organisations. Analysing the autonomy of women’s development organisations − particularly in close collaboration with their members − is a complementary approach to the one focused on solving the often-material constraints that hamper their development. This complementary approach will help focus on how to strengthen their capacity to be in the driver’s seat in defining their goals and strategies and to become fully-fledged partners of support organisations.